Factores motivacionales de los trabajadores en algunas pymes de marketing en la ciudad de Bogotá - Orjuela Martin, Jhon Alexander (Universidad Antonio Nariño, 2023)
Motivation is generally perceived as motives or reasons, whether internal or external, that lead the person to an action, where understanding the perceptions of the desires and needs of the work teams can improve productivity, commitment and talent retention. in the organizations, being these, frequent difficulties in our area of interest, for that reason an investigation is approached that allows to know the forms of motivation of the marketing SMEs located in the city of Bogotá, seeking to know the processes that allow to improve the productivity and commitment of the work teams of the sector through the proposal by Ryan and Deci on selfdetermination, in the same way it is possible to determine the level of acceptance and comfort through a Likert-type questionnaire towards aspects such as autonomy in carrying out tasks, the development of worker skills that allow maintaining or improving skills through training, rewards nsas and recognition, finding that people in this sector appreciate peer recognition more than that of their superiors, and finally the generation of a social climate with a sense of belonging and mutual support, these factors being relevant in the motivation of companies of marketing in the city of Bogota